Seasonal and monthly variation in peak expiratory flow rate in children with asthma - Kim, Minji; Kim, Young Min; Lee, Ji Young; Yang, Hea Kyoung; Kim, Hyunmi; Ahn, Soohyun; Baek, Sun Young; Kim, Jihyun; Ahn, Kangmo (Asia Pacific Allergy, 2021)
Background: Although understanding the seasonal patterns of asthma deterioration is important to prevent asthma exacerbation, previous approaches have limitations in evaluating the actual trend of asthma exacerbation. Objective: This study aimed to evaluate the seasonal and monthly variations in the peak expiratory flow rate (PEFR) among children with asthma. Methods: A total of 89 patients with asthma were enrolled between December 2012 and March 2015. The PEFR in the morning and evening was recorded daily, and the percentage change in PEFR from baseline was calculated. Generalized estimating equation models were constructed after adjusting for age, sex, body mass index, and sensitization to house dust mites or pollen. Results: The PEFR records of 11,222 person-days showed a significant decrease in the morning and evening in autumn than in winter by -1.9% (95% confidence interval [CI], -3.73 to -0.15) and -2.1% (95% CI, -3.80 to -0.37), respectively. The morning PEFR was significantly lower in April, August, October, and December than in January with changes of -4.2% (95% CI, -7.08 to -1.23) in April, -3.1% (95% CI, -5.79 to -0.47) in August, -3.7% (95% CI, -6.09 to -1.21) in October, and -1.9% (95% CI, -3.62 to -0.12) in December. The percentage change of evening PEFR significantly decreased by -3.3% (95% CI, -6.38 to -0.25) in April and by -3.3% (95% CI, -5.56 to -1.07) in October. Conclusion: The PEFR in children with asthma was lower in autumn than in winter. In terms of monthly patterns, the PEFR was significantly reduced in April and October than in January. These results can serve as a basis for preventing asthma exacerbations by developing seasonal or monthly management strategies for children with asthma.
Keywords: Asthma; Child; Month; Peak expiratory flow rate; Seasonal variation